2005
DOI: 10.1007/s10295-005-0021-z
|View full text |Cite
|
Sign up to set email alerts
|

Active site residues controlling substrate specificity in 2-nitrotoluene dioxygenase from Acidovorax sp. strain JS42

Abstract: Acidovorax (formerly Pseudomonas) sp. strain JS42 utilizes 2-nitrotoluene as sole carbon, nitrogen, and energy source. 2-Nitrotoluene 2,3-dioxygenase (2NTDO) catalyzes the initial step in 2-nitrotoluene degradation by converting 2-nitrotoluene to 3-methylcatechol. In this study, we identified specific amino acids at the active site that control specificity. The residue at position 350 was found to be critical in determining both the enantiospecificity of 2NTDO with naphthalene and the ability to oxidize the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…Mutation of Asn258 to a Val in NBDO changed the regioselectivity of product formation (12). In Oxy, although the original and substituted residues are both hydrophobic, nevertheless, the mutation affected substrate specificity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutation of Asn258 to a Val in NBDO changed the regioselectivity of product formation (12). In Oxy, although the original and substituted residues are both hydrophobic, nevertheless, the mutation affected substrate specificity.…”
Section: Resultsmentioning
confidence: 99%
“…This process is called lateral dioxygenation. The amino acid residues that affect the substrate specificity of ROs have been identified (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). In these studies, the molecular mechanism by which substrate specificity is altered has been discussed on the basis of proposed structural similarities or molecular simulation.…”
mentioning
confidence: 99%
“…The amino group of Asn-258 forms a hydrogen bond with the nitro groups of nitrobenzene and 3NT based on NBDO crystal structure data (6) and is required for efficient attack at the nitro-substituted carbon of nitroarene substrates in NBDO ( Fig. 2 and Table 2) and 2NTDO (18). Interestingly, DNTDOs do not have an asparagine at position 258 (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…This residue has been shown to be important for determining substrate specificity in several different dioxygenases (15,16,18,(30)(31)(32)47). Changes in product ratios formed by the I350F mutant can be attributed to the increased size of the residue.…”
Section: Discussionmentioning
confidence: 99%
“…strain 9816-4 (143). Mutagenesis studies revealed that specificity is controlled by the C-terminal half of the dioxygenase (144), and like the case in NBDO (91), the asparagine at position 258 is critical for proper positioning of substrates in the active site for oxidative removal of the nitro group (107). A divergently transcribed LysR-type regulator activates transcription of the 2NTDO genes in response to nitroaromatic compounds (89,112).…”
Section: Pathways For Nitrotoluene Catabolismmentioning
confidence: 99%